Corporate social responsibility: Manchester United FC and Liverpool FC - Tobar, Felipe Bertazzo (2021)
Football, beyond its intrinsic nature as a sporting activity, is a social and cultural phenomenon that requires interdisciplinary analysis to comprehend its development. If this theoretical exercise is per se a challenge in normal times, it only increases through uncertainty periods as faced during the COVID-19 pandemic. Normally characterized within the category of "events beyond human control," this pandemic has impacted football clubs form both a financial and social perspective, forcing directors to take unprecedented decisions linked to integrity and accountability, which ultimately revealed whether or not the intrinsic institutional values of their clubs were preserved.